Bacteria‐Triggered Multifunctional Hydrogel for Localized Chemodynamic and Low‐Temperature Photothermal Sterilization. Issue 51 (13th October 2021) - Lin, Xiaodong; Fang, Yuan; Hao, Zhe; Wu, Haotian; Zhao, Minyang; Wang, Shuo; Liu, Yaqing
Abstract: Pathogenic infections seriously threaten public health and have been considered as one of the most critical challenges in clinical therapy. Construction of a safe and efficient photothermal antibacterial platform is a promising strategy for treatment of bacterial infections. Considering that high temperature does harm to the normal tissues and cells, herein, a bacteria‐triggered multifunctional hydrogel is constructed for low‐temperature photothermal sterilization with high efficiency by integrating localized chemodynamic therapy (L‐CDT). The hydrogel is constructed by incorporating copper sulfide nanoparticles (CuSNPs ) with photothermal profile into the network of hyaluronic acid (HA) and Fe 3+ ‐EDTA complexes, named as CHFH (CuSNPs ‐HA‐Fe 3+ ‐EDTA hydrogel). Bacteria can be accumulated on the surface of CHFH, which secretes hyaluronidase to decompose the HA and release Fe 3+ . The Fe 3+ is reduced into Fe 2+ in microenvironment of bacteria to trigger Fenton reaction. The generated hydroxyl radicals result in sterilization based on L‐CDT within short range. By integrating with photothermal property of CuSNPs, low‐temperature photothermal therapy (LT‐PTT) for sterilization is realized, which improves the antibacterial efficiency while minimizes damage to normal tissues. The CHFH is further used to prepare Band aid which effectively promotes the Staphylococcus aureus ‐infected wound healing process in vivo, confirming the great potential for clinical application. Abstract : By integrating the localized chemodynamic therapy, the as‐prepared CHFH can high efficiently eliminate bacteria via photothermal therapy at low temperature, which has no obvious damage to the normal tissues and cells. The CHFH‐based Band aid is further applied to promote wound healing of bacterially infected mice in vivo, realizing efficient debridement and improving tissue reconstruction.